THE IMPACT OF CUSTOMER VALUE PROPOSITION TOWARDS PURCHASE INTENTION OF CHESA CUP - Gretna Kusuma Putra; Richard Harijanto (iBuss Management, 2015)
Instant food has become an important part in the daily life of Indonesian. Therefore, many manufacturers competing to make innovative and suitable instant food product for Indonesians. Instant food market has been dominated by Indonesian instant noodle product of PT Indofood Sukses Makmur which is Indomie. This makes Bogasari as one of PT ISM Subsidiaries interested to enter this market and launched Chesa Cup, an instant cake products. Research was conducted to analyze the impact of Customer Value Proposition of Chesa Cup product toward customer purchase intention. Data obtained by simple random sampling method, by distributing it to 100 respondents in the area of Surabaya and the data processed by Multiple Regression Analysis. As a result, the overall Customer Value Proposition influence customer purchase intention simultaneously, with functional and economic value of the product have the significant impact on customer purchase intention. Keywords: Customer Value Proposition, Purchase Intention, Multiple Regression Analysis.